Lithium iron manganese phosphate composite material and preparation method thereof, positive electrode sheet, battery and electrical equipment
By introducing the first carbon layer into the lithium manganese iron phosphate nanoparticles to form a conductive network, the problems of high water absorption, large impedance and low volatility of the lithium manganese iron phosphate material are solved, and the particle size of the material is increased and the water absorption rate is achieved. and the improvement of electrochemical performance.
Patent Information
- Application Number
- CN202210977874.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-08-16
AI Technical Summary
The existing lithium manganese ferrophosphate materials have high water absorption, resulting in poor storage capacity retention of batteries, and their impedance is large and their capacity volatility is low.
By mixing and dispersing the lithium manganese iron phosphate nanoparticles with the binder nanoparticles, heat treatment is performed to melt and carbonize the binder nanoparticles to form a first carbon layer connecting the lithium manganese iron phosphate nanoparticles, and an internal one with Large-particle lithium manganese iron phosphate composite material of conductive network.
The particle size and specific surface area of the lithium manganese iron phosphate composite material are improved, the water absorption rate is reduced, the conductivity is improved, the impedance is reduced, and the capacity is increased, thereby improving the energy density and electrochemical performance of the battery.
Smart Images

Figure CN115939330B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to a lithium iron manganese phosphate composite material and a preparation method thereof, a positive electrode sheet, a battery and electrical equipment. Background Art
[0002] Lithium manganese iron phosphate positive electrode material is a solid solution material composed of lithium iron phosphate and lithium manganese phosphate. It has the characteristics of high operating voltage platform, high energy density, low cost, good thermal stability and chemical stability. It is one of the mainstream positive electrode materials currently being researched.
[0003] The particle size of existing lithium iron manganese phosphate materials is generally controlled at the nanometer level, and their specific surface area is relatively large. Once exposed to humid air, moisture is easy to contact the hydrophilic Li phase on the surface of the material. After a period of time (a few weeks), the surface lithium of lithium iron phosphate will also react with water to cause lithium iron phosphate to increase its water content. When this lithium iron manganese phosphate material with a relatively high water content is used as a positive electrode material for a battery, the water in the material is difficult to remove during the subsequent battery mixing and slurrying process, and will remain in the battery, which makes the battery storage capacity retention rate mostly poor.
[0004] If nano-sized lithium manganese iron phosphate materials are used as primary particles, or larger-sized secondary particles, although the water absorption rate can be reduced to a certain extent, it will cause problems such as high impedance and low specific capacity volatility. Summary of the invention
[0005] In view of the above problems, the present application proposes a lithium iron manganese phosphate composite material and its preparation method, positive electrode plate, battery and electrical equipment, which can improve the technical problems of high impedance and low specific capacity volatility while improving the high water absorption rate of lithium iron manganese phosphate.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron manganese phosphate composite material, which includes the following steps: mixing and evenly dispersing lithium iron manganese phosphate nanoparticles and binder nanoparticles to obtain a mixed powder; heat treating the mixed powder under an inert atmosphere so that the binder nanoparticles first melt to bond the lithium iron manganese phosphate nanoparticles, and then carbonize and form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles to obtain the lithium iron manganese phosphate composite material; wherein the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1).
[0007] In the technical solution of the embodiment of the present application, the binder nanoparticles can be melted first by heat treating the mixed powder. Since the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1) at this time, the binder nanoparticles can only be distributed in a limited space in the mixed powder, resulting in some areas inevitably containing no binder nanoparticles. Therefore, no additional treatment is required, and the particle size of the secondary particles can be limited by directly heat treating the evenly mixed mixed powder to prevent the particle size from being too large. During the heat treatment process, the binder nanoparticles in the mixed powder first melt to generate bonding force, and bond to the lithium iron manganese phosphate nanoparticles around it to form a large-particle intermediate product. Then, without additional treatment, the binder nanoparticles inside the large-particle intermediate product are carbonized at the heat treatment temperature to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, so that a large-particle lithium iron manganese phosphate composite material with a conductive network composed of the first carbon layer inside can be obtained, thereby not only increasing the particle size of the lithium iron manganese phosphate composite material and reducing its specific surface area, improving the problem of high water absorption caused by the small particle size and excessive specific surface area of the lithium iron manganese phosphate nanoparticles, but also utilizing the conductive network formed by the first carbon layer inside it to effectively improve the conductivity of the lithium iron manganese phosphate composite material, reduce impedance and increase its capacity, increase the battery energy density, and effectively improve the electrochemical performance of the material.
[0008] In some embodiments, the melting temperature of the binder nanoparticles is lower than the temperature of the heat treatment. With the above arrangement, the binder nanoparticles can be first melted to bind the lithium iron manganese phosphate nanoparticles at the heat treatment temperature, and then carbonized to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, which simplifies the preparation process and effectively improves the preparation efficiency.
[0009] In some embodiments, the heat treatment temperature is 400-1000°C, and the heat treatment time is not less than 2 hours. Optionally, the heat treatment temperature is 600-1000°C, and the heat treatment time is 6-8 hours. Within the above temperature and time range, not only can the binder nanoparticles be melted first to achieve bonding, and then carbonized to form the first carbon layer, but also the above temperature range does not affect the stability and performance of lithium manganese iron phosphate.
[0010] In some embodiments, the binder nanoparticles include at least one of asphalt, phenolic resin, chitosan and cyclodextrin. The above binder has low cost, good bonding effect after melting, and low temperature required for carbonization, which can reduce energy consumption.
[0011] In some embodiments, the lithium manganese iron phosphate nanoparticles and the binder nanoparticles are mixed and dispersed uniformly by dry mixing. The dry mixing method is not only conducive to reducing energy consumption during subsequent heat treatment, but also can improve production efficiency.
[0012] In some embodiments, the step of mixing and uniformly dispersing lithium iron manganese phosphate nanoparticles and binder nanoparticles includes: placing the lithium iron manganese phosphate nanoparticles and the binder nanoparticles in a planetary stirring tank, and stirring for 30-120 minutes under the conditions of the planetary stirring tank's rotation speed of 800-1200rpm and the revolution speed of 10-30rpm. The above method can not only quickly mix and uniformly disperse the lithium iron manganese phosphate nanoparticles and the binder nanoparticles, which is conducive to controlling the particle size of the positive electrode material, but also does not involve changes in the raw material particle size during the mixing process, ensuring the integrity of the lithium iron manganese phosphate nanoparticles and improving the final electrochemical performance of the positive electrode material.
[0013] In some embodiments, the Dv50 particle size of the lithium iron manganese phosphate nanoparticles is 50-400nm. Since the lithium iron manganese phosphate nanoparticles are used as a component of the lithium iron manganese phosphate composite material, the particle size of the lithium iron manganese phosphate nanoparticles within this range is reasonably selected, which is not only easy to obtain, but also can reduce the impedance of the prepared lithium iron manganese phosphate composite material, and improve the lithium ion transmission efficiency and electron conduction efficiency. If the particle size of the lithium iron manganese phosphate nanoparticles is too small, it is difficult to synthesize and is not easy to synthesize. If the particle size of the lithium iron manganese phosphate nanoparticles is too large, the path of lithium insertion and extraction becomes longer, resulting in an increase in the impedance of the material.
[0014] In some embodiments, the particle size of the binder nanoparticles is not greater than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles, and optionally, the particle size of the binder nanoparticles is ≤400nm. The particle size of the binder nanoparticles is not greater than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles, which is conducive to uniform mixing of the two, and can avoid uneven particle size distribution of the formed lithium iron manganese phosphate composite material, and the presence of particles with larger particle sizes, so that the Dv99 of the lithium iron manganese phosphate composite material is too large to affect its performance.
[0015] In some embodiments, the lithium iron manganese phosphate nanoparticles include a lithium iron manganese phosphate core and a second carbon layer coated on the surface of the lithium iron manganese phosphate core. The introduction of the second carbon layer can improve the conductivity of the lithium iron manganese phosphate nanoparticles, reduce the impedance of the lithium iron manganese phosphate nanoparticles, and improve their specific capacity. When the lithium iron manganese phosphate nanoparticles are used as raw materials for lithium iron manganese phosphate composite materials, the impedance of the lithium iron manganese phosphate composite materials can be further reduced, the specific capacity can be improved, and the electrochemical performance can be improved.
[0016] In some embodiments, the thickness of the second carbon layer is 2-20 nm. The second carbon layer within the above thickness range can effectively improve the conductivity of the lithium manganese iron phosphate core as a conductive layer. If the second carbon layer is too thin, good conductivity cannot be guaranteed; if the second carbon layer is too thick, the carbon weight ratio will increase, affecting the gram capacity of the material.
[0017] In some embodiments, the chemical formula of the lithium iron manganese phosphate core is LiMn1-x Fe x PO4, wherein x=0.05-0.95; optionally, x=0.4-0.6. The above lithium manganese iron phosphate core is easy to prepare and reduces the difficulty of obtaining.
[0018] In a second aspect, the present application provides a lithium iron manganese phosphate composite material, which is prepared by the preparation method in the above embodiment, and the particle size of the lithium iron manganese phosphate composite material is micron level.
[0019] In the technical solution of the embodiment of the present application, a lithium iron manganese phosphate composite material having a conductive network composed of a first carbon layer inside is obtained by the preparation method provided in the above embodiment, thereby not only increasing the particle size of the lithium iron manganese phosphate composite material and reducing its specific surface area, improving the problem of high water absorption caused by the small particle size and excessive specific surface area of the lithium iron manganese phosphate nanoparticles, but also utilizing the conductive network formed by the first carbon layer inside it to effectively improve the conductivity of the lithium iron manganese phosphate composite material, reduce impedance and increase its capacity.
[0020] In some embodiments, the Dv50 particle size of the lithium manganese iron phosphate composite material is 2-5 μm, and the Dv99 particle size is ≤14 μm. The lithium manganese iron phosphate composite material has a reasonable particle size distribution and a uniform particle size, so that when it is used in an electrode sheet, the electrochemical performance of the electrode sheet can be optimized.
[0021] In a third aspect, the present application provides a positive electrode plate, which includes a current collector and a positive electrode film layer formed on the surface of the current collector, and the positive electrode film layer contains the lithium manganese iron phosphate composite material in the above embodiment.
[0022] In a fourth aspect, the present application provides a battery, which includes the positive electrode plate in the above embodiment.
[0023] In a fifth aspect, the present application provides an electrical device, which includes the battery in the above embodiment, and the battery is used to provide electrical energy.
[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0026] Figure 1A schematic diagram of the structure of a vehicle according to some embodiments of the present application;
[0027] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;
[0028] Figure 3 A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;
[0029] Figure 4 This is a schematic diagram of the structure of the positive electrode sheet of some embodiments of the present application;
[0030] Figure 5 This is a schematic diagram of the preparation process of lithium iron manganese phosphate composite materials according to some embodiments of the present application.
[0031] The reference numerals in the specific implementation manner are as follows:
[0032] 1000-Vehicles;
[0033] 100-battery; 200-controller; 300-motor;
[0034] 10-box; 11-first part; 12-second part;
[0035] 20-battery cell; 21-end cover; 21a-electrode terminal; 22-housing; 23-electrode assembly; 23a-electrode ear;
[0036] 231 - positive electrode plate; 2311 - current collector; 2313 - positive electrode film layer. DETAILED DESCRIPTION
[0037] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0039] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0040] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0041] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0042] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0043] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0044] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0045] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.
[0046] The inventors have noticed that if nano-sized lithium manganese iron phosphate materials are used as primary particles, or secondary particles with larger particle sizes, although the water absorption rate can be reduced to a certain extent, the impedance will be large and the specific capacity volatility will be low. Although the above problems can be improved to a certain extent by agglomerating lithium manganese iron phosphate nanoparticles and mixing them with a conductive agent to obtain secondary particles, since the conductive agent is added after the secondary particles are obtained, the primary particles inside the secondary particles cannot exert their capacity due to poor conductivity and have a large impedance.
[0047] Based on the above considerations, in order to improve the technical problems of high impedance and low volatile specific capacity of lithium iron manganese phosphate while taking into account the high water absorption rate of lithium iron manganese phosphate, the inventors have designed a method for preparing a positive electrode material after in-depth research, which includes the following steps: mixing and evenly dispersing lithium iron manganese phosphate nanoparticles and binder nanoparticles to obtain a mixed powder; heat-treating the mixed powder under an inert atmosphere so that the binder nanoparticles first melt to bond the lithium iron manganese phosphate nanoparticles, and then carbonizing and forming a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, to obtain a lithium iron manganese phosphate composite material as a positive electrode material; wherein the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1).
[0048] In the preparation method, the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1), that is, a small amount of binder nanoparticles and a large amount of lithium iron manganese phosphate nanoparticles are mixed evenly and then heat-treated, so that the lithium iron manganese phosphate nanoparticles are first bonded by the binder nanoparticles to form a large particle intermediate product, and then the binder nanoparticles inside the large particle intermediate product are carbonized at the heat treatment temperature to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, and finally a lithium iron manganese phosphate composite material with a conductive network (composed of the first carbon layer) inside is obtained, thereby not only increasing the particle size of the lithium iron manganese phosphate composite material and reducing its specific surface area, but also improving the problem of high water absorption caused by the small particle size and excessive specific surface area of the lithium iron manganese phosphate nanoparticles, and utilizing the conductive network formed by the first carbon layer inside to effectively improve the conductivity of the lithium iron manganese phosphate composite material, reduce impedance and increase its capacity.
[0049] The battery cell disclosed in the embodiment of the present application can be used in, but not limited to, electric devices such as vehicles, ships or aircraft. A power supply system comprising the battery cell and battery disclosed in the present application can be used to form the electric device, which is beneficial to improve the technical problems of high impedance and low volatile capacity of lithium manganese iron phosphate on the basis of improving its high water absorption rate, thereby improving the stability of battery performance and energy density.
[0050] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0051] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0052] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0053] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0054] Please refer to Figure 2 , Figure 2An exploded view of a battery 100 provided in some embodiments of the present application. The battery 100 includes a housing 10 and a battery cell 20, and the battery cell 20 is contained in the housing 10. The housing 10 is used to provide a storage space for the battery cell 20, and the housing 10 can adopt a variety of structures. In some embodiments, the housing 10 can include a first part 11 and a second part 12, and the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 can be a hollow structure with one end open, and the first part 11 can be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the housing 10 formed by the first part 11 and the second part 12 can be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0055] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.
[0056] Each battery cell 20 may be a secondary battery or a primary battery. The battery cell 20 may be cylindrical, flat, rectangular or in other shapes.
[0057] Please refer to Figure 3 , Figure 3 The schematic diagram of the exploded structure of the battery cell 20 provided in some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.
[0058] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0059] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0060] The electrode assembly 23 is a component in the battery cell 20 where electrochemical reactions occur. One or more electrode assemblies 23 may be included in the housing 22. The electrode assembly 23 is mainly formed by winding or stacking a positive electrode sheet 231 and a negative electrode sheet, and a separator is usually provided between the positive electrode sheet 231 and the negative electrode sheet. The parts of the positive electrode sheet 231 and the negative electrode sheet with active materials constitute the main body of the electrode assembly, and the parts of the positive electrode sheet 231 and the negative electrode sheet without active materials each constitute a tab 23a. The positive tab and the negative tab may be located together at one end of the main body or at both ends of the main body respectively. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 23a connects the electrode terminal to form a current loop.
[0061] See also Figure 4 The positive electrode sheet 231 includes a current collector 2311 and a positive electrode film layer 2313 formed on the surface of the current collector 2311 , and the positive electrode film layer 2313 contains a manganese iron lithium phosphate composite material.
[0062] Among them, the lithium manganese iron phosphate composite material is used as the positive electrode active material to react with the electrolyte during the charging and discharging process of the battery.
[0063] It should be noted that, in addition to the lithium manganese iron phosphate composite material, the positive electrode film layer 2313 may also contain a conductive agent, a binder and optionally other positive electrode active materials. Those skilled in the art may make a selection according to actual needs and no limitation is made here.
[0064] See also Figure 5 According to some embodiments of the present application, optionally, a method for preparing a lithium iron manganese phosphate composite material includes the following steps: mixing and evenly dispersing lithium iron manganese phosphate nanoparticles and binder nanoparticles to obtain a mixed powder; heat-treating the mixed powder under an inert atmosphere so that the binder nanoparticles first melt to bond the lithium iron manganese phosphate nanoparticles, and then carbonize and form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, to obtain a lithium iron manganese phosphate composite material as a positive electrode material; wherein the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1).
[0065] Binder nanoparticles refer to solid nanoparticles that are solid and non-adhesive at room temperature, so that the binder nanoparticles and lithium iron manganese phosphate nanoparticles can be mixed and dispersed evenly to form a mixed powder. The binder nanoparticles contain carbon elements, and their melting temperature is lower than their carbonization temperature, so that they can melt first during heat treatment to generate bonding force, and after bonding the lithium iron manganese phosphate nanoparticles, they can be carbonized to form a first carbon layer.
[0066] The inert atmosphere includes but is not limited to nitrogen atmosphere, and can also be argon atmosphere or a mixture of the two. The inert atmosphere can be used to carbonize the binder nanoparticles under oxygen-deficient conditions to form a first carbon layer located inside the lithium manganese iron phosphate composite material, that is, the first carbon layer not only connects the lithium manganese iron phosphate nanoparticles to improve the stability of the lithium manganese iron phosphate composite material, but also forms a conductive network inside the lithium manganese iron phosphate composite material to reduce its impedance and increase its gram capacity volatilization, thereby increasing energy density.
[0067] Since the raw materials are lithium iron manganese phosphate nanoparticles and binder nanoparticles, both of which are relatively small, and the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1), in the mixed powder obtained after the two are mixed and evenly dispersed, the periphery of each binder nanoparticle is basically evenly distributed with lithium iron manganese phosphate nanoparticles. Therefore, during the subsequent heat treatment, the internal binder nanoparticles can be melted first to bond with the lithium iron manganese phosphate nanoparticles around them to form an intermediate product of large particles, and no compacted state will be formed, which is beneficial to obtaining a granular lithium iron manganese phosphate composite material and is beneficial to controlling the particle size of the lithium iron manganese phosphate composite material.
[0068] That is, in the technical solution of the embodiment of the present application, the binder nanoparticles can be melted first by heat treating the mixed powder. Since the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1) at this time, the binder nanoparticles can only be distributed in a limited space in the mixed powder, resulting in some areas inevitably containing no binder nanoparticles. Therefore, no additional treatment is required, and the particle size of the secondary particles can be limited by directly heat treating the evenly mixed mixed powder to prevent the particle size from being too large. During the heat treatment process, the binder nanoparticles in the mixed powder first melt to generate bonding force, and bond to the lithium iron manganese phosphate nanoparticles around it to form a large-particle intermediate product. Then, without additional treatment, the binder nanoparticles inside the large-particle intermediate product are carbonized at the heat treatment temperature to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, so that a large-particle lithium iron manganese phosphate composite material with a conductive network composed of the first carbon layer inside can be obtained, thereby not only increasing the particle size of the lithium iron manganese phosphate composite material and reducing its specific surface area, improving the problem of high water absorption caused by the small particle size and excessive specific surface area of the lithium iron manganese phosphate nanoparticles, but also utilizing the conductive network formed by the first carbon layer inside it to effectively improve the conductivity of the lithium iron manganese phosphate composite material, reduce impedance and increase its capacity, increase the battery energy density, and effectively improve the electrochemical performance of the material.
[0069] Exemplarily, the weight ratio of the binder nanoparticles to the lithium manganese iron phosphate nanoparticles is any value of 0.05:1, 0.07:1, 0.10:1, 0.12:1, 0.15:1, 0.17:1, 0.20:1, or between any two values.
[0070] According to some embodiments of the present application, optionally, the melting temperature of the binder nanoparticles is lower than the temperature of the heat treatment.
[0071] By using the above arrangement, it can be achieved that at the heat treatment temperature, the binder nanoparticles first melt to bond the lithium iron manganese phosphate nanoparticles, and then carbonize to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles. The preparation process is simple and the preparation efficiency is effectively improved.
[0072] According to some embodiments of the present application, optionally, the temperature of the heat treatment is 400-1000° C., and the time of the heat treatment is not less than 2 hours.
[0073] Within the above temperature and time range, not only can the binder nanoparticles be melted first to achieve bonding, and then carbonized to form a first carbon layer, but the above temperature range also does not affect the stability and performance of lithium manganese iron phosphate.
[0074] The time and temperature of the heat treatment can be actually selected according to the actual choice of the binder.
[0075] Illustratively, the temperature of the heat treatment is any one of 400° C., 500° C., 600° C., 700° C., 800° C., 900° C., 1000° C., or between any two values.
[0076] Optionally, the heat treatment temperature is 600-1000° C., and the heat treatment time is 6-8 hours.
[0077] Exemplarily, the heat treatment time is any one of 4.0 h, 4.5 h, 5.0 h, 5.5 h, 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h or between any two values.
[0078] According to some embodiments of the present application, optionally, the binder nanoparticles include at least one of asphalt, phenolic resin, chitosan and cyclodextrin.
[0079] The above-mentioned adhesive has low cost, good bonding effect after melting, and low temperature required for carbonization, which can reduce energy consumption.
[0080] Exemplarily, the binder nanoparticles are asphalt, or the binder nanoparticles are phenolic resin, or a mixture of the two, and so on.
[0081] It should be noted that the lithium manganese iron phosphate nanoparticles and the binder nanoparticles can be mixed and dispersed uniformly by dry mixing, or by placing the two in a dispersion, stirring and then drying, wherein the lithium manganese iron phosphate nanoparticles and the binder nanoparticles are both insoluble in the dispersion.
[0082] According to some embodiments of the present application, optionally, the method of mixing and uniformly dispersing the lithium manganese iron phosphate nanoparticles and the binder nanoparticles is dry mixing.
[0083] Dry mixing refers to directly mixing lithium manganese iron phosphate nanoparticles with binder nanoparticles without introducing a dispersion liquid.
[0084] The dry mixing method is not only beneficial to reducing energy consumption during subsequent heat treatment, but also can improve production efficiency.
[0085] There are many ways of dry mixing, such as stirring mixing, grinding mixing, etc. Since the grinding mixing method will affect the particle size and shape of the lithium manganese iron phosphate nanoparticles, the dry mixing method can be optionally stirring mixing.
[0086] According to some embodiments of the present application, optionally, the step of mixing and uniformly dispersing lithium manganese iron phosphate nanoparticles and binder nanoparticles includes: placing the lithium manganese iron phosphate nanoparticles and the binder nanoparticles in a planetary stirring tank, and stirring for 30-120 minutes under the conditions of the planetary stirring tank's rotation speed of 800-1200rpm and the revolution speed of 10-30rpm.
[0087] The above method can not only quickly mix and evenly disperse the lithium iron manganese phosphate nanoparticles and the binder nanoparticles, which is beneficial to control the particle size of the positive electrode material, but also does not involve changes in the particle size of the raw materials during the mixing process, thereby ensuring the integrity of the lithium iron manganese phosphate nanoparticles and improving the final electrochemical properties of the positive electrode material.
[0088] Exemplarily, the rotation speed of the planetary stirring tank is any value of 800rpm, 850rpm, 900rpm, 950rpm, 1000rpm, 1050rpm, 1100rpm, 1150rpm, 1200rpm or between any two values, the revolution speed is any value of 10rpm, 12, 15, 17, 20rpm, 23rpm, 25rpm, 27rpm, 30rpm or between any two values, and the stirring time is any value of 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min or between any two values.
[0089] According to some embodiments of the present application, optionally, the Dv50 particle size of the lithium manganese iron phosphate nanoparticles is 50-400 nm.
[0090] Dv50 particle size refers to the particle size at which the cumulative distribution of particles is 50%, also called the median diameter or median particle size.
[0091] Since lithium iron phosphate nanoparticles are a component of lithium iron phosphate composite materials, the particle size of lithium iron phosphate nanoparticles within this range is reasonably selected. They are not only easy to obtain, but also can reduce the impedance of the prepared lithium iron phosphate composite materials and improve the lithium ion transmission efficiency and electron conduction efficiency. If the particle size of the lithium iron phosphate nanoparticles is too small, it is difficult to synthesize them. If the particle size of the lithium iron phosphate nanoparticles is too large, the path of lithium insertion and extraction becomes longer, resulting in an increase in the impedance of the material.
[0092] According to some embodiments of the present application, optionally, the particle size of the binder nanoparticles is not greater than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles.
[0093] The particle size of the binder nanoparticles is not larger than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles, which is conducive to uniform mixing of the two and can avoid uneven particle size distribution of the formed lithium iron manganese phosphate composite material and the presence of larger particles, which will cause the Dv90 of the lithium iron manganese phosphate composite material to be too large and affect its performance.
[0094] Since the Dv50 particle size of the lithium iron manganese phosphate nanoparticles is 50-400 nm, optionally, the particle size of the binder nanoparticles is ≤400 nm.
[0095] According to some embodiments of the present application, optionally, the lithium iron manganese phosphate nanoparticles include a lithium iron manganese phosphate core and a second carbon layer coated on the surface of the lithium iron manganese phosphate core.
[0096] That is, the lithium iron phosphate nanoparticles have a core-shell structure, and the second carbon layer can be more evenly and completely coated on the surface of the lithium iron phosphate core, which not only blocks its contact with moisture, improves the water absorption performance of the lithium iron phosphate core, but also effectively improves the conductivity of the lithium iron phosphate nanoparticles.
[0097] It can be understood that the second carbon layer is a carbon layer existing in the lithium iron manganese phosphate nanoparticles themselves, that is, it exists in the lithium iron manganese phosphate nanoparticles before the mixed powder is obtained.
[0098] That is, by introducing the second carbon layer, the conductivity of the lithium iron manganese phosphate nanoparticles can be improved, the impedance of the lithium iron manganese phosphate nanoparticles can be reduced, and their specific capacity can be improved. When it is used as a raw material for a lithium iron manganese phosphate composite material, the impedance of the lithium iron manganese phosphate composite material can be further reduced, its specific capacity can be improved, and its electrochemical performance can be improved.
[0099] According to some embodiments of the present application, optionally, the thickness of the second carbon layer is 2-20 nm.
[0100] The thickness of the second carbon layer refers to the distance between a side of the second carbon layer connected to the lithium iron manganese phosphate core and a side of the second carbon layer away from the lithium iron manganese phosphate core.
[0101] The second carbon layer within the above thickness range can serve as a conductive layer and effectively improve the conductivity of the lithium manganese iron phosphate core. If the second carbon layer is too thin, good conductivity cannot be guaranteed; if the second carbon layer is too thick, the carbon weight ratio will increase, affecting the gram capacity of the material.
[0102] Illustratively, the thickness of the second carbon layer is any value of 2 nm, 5 nm, 7 nm, 10 nm, 13 nm, 15 nm, 18 nm, and 20 nm, or is between any two values.
[0103] According to some embodiments of the present application, optionally, the chemical formula of lithium manganese iron phosphate is LiMn 1-x Fe x PO4, where x = 0.05-0.95.
[0104] That is, no matter whether the second carbon layer is coated or not, the chemical formula of lithium manganese iron phosphate is as shown above. The above lithium manganese iron phosphate is easy to prepare and can reduce the difficulty of obtaining.
[0105] Illustratively, x=any value among 0.05, 0.1, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or between any two values.
[0106] Optionally, x=0.4-0.6.
[0107] According to some embodiments of the present application, the present application further provides a lithium iron manganese phosphate composite material, which is prepared by the preparation method of any of the above schemes, and the particle size of the lithium iron manganese phosphate composite material is micron level.
[0108] In the technical solution of the embodiment of the present application, a large-particle lithium iron manganese phosphate composite material having a conductive network composed of a first carbon layer inside is obtained by the preparation method provided in the above embodiment, thereby not only increasing the particle size of the lithium iron manganese phosphate composite material and reducing its specific surface area, but also improving the problem of high water absorption caused by the small particle size and excessive specific surface area of the lithium iron manganese phosphate nanoparticles, and utilizing the conductive network formed by the first carbon layer inside it to effectively improve the conductivity of the lithium iron manganese phosphate composite material, reduce impedance and increase its capacity.
[0109] According to some embodiments of the present application, optionally, the Dv50 particle size of the lithium manganese iron phosphate composite material is 2-5 μm, and the Dv99 particle size is ≤14 μm.
[0110] The Dv50 particle size refers to the particle size at which the cumulative distribution of particles is 50%, also called the median diameter or median particle size. The Dv99 particle size refers to the particle size at which the cumulative distribution of particles is 99%.
[0111] The particle size distribution of the lithium manganese iron phosphate composite material is reasonable and the prepared particle size is uniform, so that when it is used in an electrode sheet, the electrochemical performance of the electrode sheet can be optimized.
[0112] Exemplarily, the Dv50 particle size of the lithium manganese iron phosphate composite material is any value of 2 μm, 3 μm, 4 μm, 5 μm, or between any two values.
[0113] According to some embodiments of the present application, the present application also provides a positive electrode plate, which includes a current collector and a positive electrode film layer formed on the surface of the current collector, and the positive electrode film layer contains the lithium manganese iron phosphate composite material provided by any of the above schemes.
[0114] According to some embodiments of the present application, the present application also provides a battery, comprising the positive electrode plate provided by any of the above schemes.
[0115] According to some embodiments of the present application, the present application further provides an electrical device, comprising a battery provided by any of the above schemes, and the battery is used to provide electrical energy to the electrical device.
[0116] The power-consuming device may be any of the aforementioned devices or systems using batteries.
[0117] Some specific embodiments are listed below to better illustrate the present application.
[0118] Examples and Comparative Examples
[0119]
Preparation of positive electrode
[0120] Current collector: aluminum foil.
[0121] Preparation of lithium iron manganese phosphate composite materials in various embodiments and comparative examples: lithium iron manganese phosphate nanoparticles and binder nanoparticles as shown in Table 1 are placed in a mixing tank of a planetary mixer, mixed and evenly dispersed under the parameters shown in Table 1, and then heat treated under N2 atmosphere protection to obtain lithium iron manganese phosphate composite materials.
[0122] The lithium manganese iron phosphate composite material, PVDF (polyvinylidene fluoride) binder, and conductive carbon black prepared in each embodiment and comparative example were mixed in a mass ratio of 96:2:2 and added to NMP (N-methylpyrrolidone), and the solid content was adjusted to 70%. The positive electrode slurry was obtained, and the positive electrode slurry was evenly coated on aluminum foil, and baked and dried at 120°C to obtain the positive electrode sheets corresponding to each embodiment and comparative example.
[0123]
Preparation of negative electrode sheet
[0124] A negative electrode slurry consisting of 97 wt% graphite, 1 wt% conductive carbon black and 2 wt% styrene-butadiene rubber is coated on a negative electrode current collector, and the mixture is dried and rolled.
[0125]
Diaphragm
[0126] Polyvinylidene fluoride.
[0127]
Electrolyte
[0128] 1mol / LLiPF6 / (EC+DMC) (wherein LiPF6 is lithium hexafluorophosphate, EC is ethylene carbonate, DMC is dimethyl carbonate, and the volume ratio of EC to DMC is 1:1).
[0129]
Preparation of lithium-ion batteries
[0130] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the tabs are welded to the bare cell, and the bare cell is placed in an aluminum shell to assemble into a dry cell. The dry cell is baked in a vacuum oven at 100°C to remove water for 8 hours, and then the water content of the positive electrode sheet is tested. The results are shown in Table 2. The baking is continued until the water content of the positive electrode sheet is <500ppm, and then the electrolyte is injected. After formation, a lithium-ion battery is obtained.
[0131] test:
[0132] The discharge capacity of each lithium-ion battery at 0.33C was obtained by testing (the lithium-ion battery was charged to 4.3V at a constant current of 0.33C at 25°C, then charged at a constant voltage of 4.3V until the current dropped to 0.05C, and then discharged to 2.5V at a constant current of 0.33C to obtain the discharge capacity), and the gram capacity of the material was calculated based on the weight of the lithium iron manganese phosphate material used (the weight was calculated by calculating the positive electrode weight through the length of the cathode electrode piece used in the battery and the coating weight and multiplying it by the proportion of lithium iron manganese phosphate in the positive electrode).
[0133] The DC resistance value DCR of the lithium-ion battery was obtained by testing (charged to 4.3V at a constant current of 0.33C at 25°C, then charged at a constant voltage of 4.3V until the current dropped to 0.05C, and then discharged at a constant current of 0.33C to half of the aforementioned 0.33C discharge capacity, i.e., adjusted to 50% SOC; then discharged at a current of 4C for 10s, and the DC resistance value of 10s was obtained by dividing the difference between the voltage before discharge and the voltage after amplification by the 4C current value). The results are shown in Table 2.
[0134] Table 1 Preparation parameters
[0135]
[0136]
[0137] Table 2 Test results
[0138]
[0139]
[0140] According to Table 1 and Table 2, the solution of the present application can improve the technical problems of high impedance and low specific capacity volatility of lithium manganese iron phosphate while taking into account the high water absorption rate of lithium manganese iron phosphate.
[0141] According to Examples 1-4 and Comparative Examples 2-3, it can be seen that the particle size of the lithium iron manganese phosphate nanoparticles has a significant effect on the size and performance of the final prepared product. When the Dv50 particle size of the lithium iron manganese phosphate nanoparticles is within the range of 50-400nm, the size of the composite lithium iron manganese phosphate obtained is reasonable, which can reduce the water absorption rate of lithium iron manganese phosphate while taking into account the reduction of DC impedance and the increase of gram capacity volatilization. If the Dv50 particle size of the lithium iron manganese phosphate nanoparticles is less than 50nm, the size of the lithium iron manganese phosphate composite material obtained is too small, and the water content of the positive electrode piece is too high after baking for 8h. If the Dv50 particle size of the lithium iron manganese phosphate nanoparticles is greater than 400nm, the size of the lithium iron manganese phosphate composite material obtained is too large, which does not meet the use requirements, and the water content of the positive electrode piece is too low after baking for 8h, resulting in a reduced gram capacity and an excessively large DC impedance value, which does not meet the use requirements.
[0142] According to Examples 1, 5-7 and Comparative Examples 4-5, when a second carbon layer exists on the surface of the lithium manganese iron phosphate nanoparticles, the thickness of the second carbon layer is in the range of 2-20 nm, which can reduce the water absorption rate of the lithium manganese iron phosphate while having a lower DC impedance and a larger specific capacity volatilization. If the thickness of the second carbon layer is too thin or too thick, its performance will be affected to a certain extent.
[0143] According to Examples 1 and 8, it can be seen that even if the type of binder nanoparticles is changed, the solution provided in the present application can still reduce the water absorption rate of lithium manganese iron phosphate and make it have lower DC impedance and larger volatile capacity per gram.
[0144] According to Examples 1, 9-11 and Comparative Examples 6-7, it can be seen that when the weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is (0.05:1)-(0.2:1), the water absorption rate of the lithium iron manganese phosphate can be effectively reduced, and it has a lower DC impedance and a larger gram capacity volatilization. The weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is too large, resulting in an excessively high content of the binder nanoparticles, resulting in the lithium iron manganese phosphate composite material being too large in size, and the positive electrode piece having too little water content after being baked for 8 hours, resulting in a DC impedance value that is too large and does not meet the use requirements. The weight ratio of the binder nanoparticles to the lithium iron manganese phosphate nanoparticles is too small, resulting in an excessively low content of the binder nanoparticles, resulting in the lithium iron manganese phosphate composite material being too small in size, and the positive electrode piece having too much water content after being baked for 8 hours.
[0145] According to Examples 1, 12-14 and Comparative Examples 8-9, it can be seen that the temperature and time of heat treatment have a significant effect on the performance of the composite lithium manganese iron phosphate.
[0146] According to Examples 15-16 and Comparative Examples 11-12, it can be seen that whether the lithium manganese iron phosphate nanoparticles are evenly dispersed after mixing with the binder nanoparticles has a significant impact on the performance of the final product. When the lithium manganese iron phosphate nanoparticles and the binder nanoparticles are placed in a planetary stirring tank, the two can be evenly dispersed under the condition that the rotation speed of the planetary stirring tank is greater than 600 rpm and the revolution speed is 10-30 rpm, and the stirring time is greater than 13 minutes, which is beneficial to improve the water absorption rate of the lithium manganese iron phosphate and reduce its DC impedance.
[0147] According to Example 17, when the raw material lithium manganese iron phosphate nanoparticles do not contain the second carbon layer, the composite lithium manganese iron phosphate is prepared in the above manner, which can also improve the technical problems of high water absorption, large impedance and low specific capacity volatility of lithium manganese iron phosphate, but the improvement effect is not as good as Examples 1 and 5-7.
[0148] According to Comparative Example 1, it can be seen that if the secondary particles obtained by directly agglomerating the lithium iron manganese phosphate nanoparticles without using the binder nanoparticles for bonding, the water content will increase significantly, which can be as high as 1280 ppm, and cannot meet the use requirements.
[0149] According to Example 1 and Comparative Example 10, it can be seen that when the particle size of the binder nanoparticles is significantly larger than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles, the prepared composite lithium iron manganese phosphate particles will be uneven, resulting in larger particles, making their Dv99 too large, resulting in increased water content, reduced gram capacity and increased DC impedance.
[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: The following steps are involved: Mixing lithium manganese iron phosphate nanoparticles and binder nanoparticles and dispersing them evenly to obtain a mixed powder; The mixed powder is heat-treated under an inert atmosphere so that the binder nanoparticles are first melted to bind the lithium iron manganese phosphate nanoparticles, and then carbonized to form a first carbon layer connecting the lithium iron manganese phosphate nanoparticles, thereby obtaining the lithium iron manganese phosphate composite material; Wherein, the weight ratio of the binder nanoparticles to the lithium manganese iron phosphate nanoparticles is (0.05:1)-(0.2:1); The temperature of the heat treatment is 400-1000°C, and the time of the heat treatment is not less than 2h.
2. The preparation method according to claim 1, characterized in that: The melting temperature of the binder nanoparticles is lower than the temperature of the heat treatment.
3. The preparation method according to claim 2, characterized in that: The heat treatment temperature is 600-1000° C., and the heat treatment time is 6-8 hours.
4. The preparation method according to claim 2, characterized in that: The binder nanoparticles include at least one of asphalt, phenolic resin, chitosan and cyclodextrin.
5. The preparation method according to claim 1, characterized in that: The method of mixing and uniformly dispersing the lithium manganese iron phosphate nanoparticles and the binder nanoparticles is dry mixing.
6. The preparation method according to claim 5, characterized in that: The step of mixing and uniformly dispersing the lithium manganese iron phosphate nanoparticles and the binder nanoparticles comprises: The lithium manganese iron phosphate nanoparticles and the binder nanoparticles are placed in a planetary stirring tank, and stirred for 30-120 minutes under the conditions that the rotation speed of the planetary stirring tank is 800-1200 rpm and the revolution speed is 10-30 rpm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The Dv50 particle size of the lithium manganese iron phosphate nanoparticles is 50-400nm.
8. The preparation method according to any one of claims 1 to 6, characterized in that: The particle size of the binder nanoparticles is not greater than the Dv50 particle size of the lithium iron manganese phosphate nanoparticles.
9. The preparation method according to any one of claims 1 to 6, characterized in that: The particle size of the binder nanoparticles is ≤400nm.
10. The preparation method according to any one of claims 1 to 6, characterized in that: The lithium iron manganese phosphate nanoparticles include a lithium iron manganese phosphate core and a second carbon layer coated on the surface of the lithium iron manganese phosphate core.
11. The preparation method according to claim 10, characterized in that: The thickness of the second carbon layer is 2-20 nm.
12. The preparation method according to claim 10, characterized in that: The chemical formula of the lithium iron manganese phosphate is LiMn 1- x Fe x PO4, where x = 0.05-0.
95.
13. The preparation method according to claim 12, characterized in that: x=0.4-0.6。 14. A lithium manganese iron phosphate composite material, characterized in that: The lithium manganese iron phosphate composite material is prepared by the preparation method according to any one of claims 1 to 13, and the particle size of the composite material is micron-level.
15. The lithium iron manganese phosphate composite material according to claim 14, characterized in that: The Dv50 particle size of the lithium manganese iron phosphate composite material is 2-5 μm, and the Dv99 particle size is ≤14 μm.
16. A positive electrode plate, characterized in that: It comprises a current collector and a positive electrode film layer formed on the surface of the current collector, wherein the positive electrode film layer contains the lithium manganese iron phosphate composite material as described in any one of claims 14-15.
17. A battery, characterized in that: Comprising the positive electrode sheet as described in claim 16.
18. An electrical equipment, characterized in that: Comprising a battery as claimed in claim 17, the battery is used to provide electrical energy.
Citation Information
Patent Citations
Preparation method of lithium ion battery and lithium ion battery
CN108039449A
Coated positive electrode material as well as preparation method and application thereof
CN114784283A